Effect of Topical versus Parentral Tranexamic Acid on Blood Loss in Spinal Deformity Surgery. A Prospective Randomized Controlled Trial. Issue 1 (April 2016) - El-Sharkawi, Mohammad; Sayed, Sherif; Gad, Wael; El-Meshtawy, Mohamed
Introduction: Massive hemorrhage and massive blood transfusion are not uncommon in spinal deformity surgery. There are many factors which may affect the perioperative blood loss. Multiple studies showed the beneficial effects of parentral tranexamic acid (TXA) in decreasing intraoperative blood loss but there is a lack of knowledge about the effect of topical use of tranexamic acid. The aim of this study is to evaluate the effect of using tranexamic acid topically versus parentrally on the amount of intra operative blood loss. Material and Methods: Between 2011 and 2014, eighty three patients (49 females/34 males, mean age 17 ± 4 ys, body weight 49 ± 6 kg) underwent correction (in the form of multiple Ponte osteotomies, PSO, PVCR) and posterior spinal fusion for spinal deformity (57 AIS, 14 congenital scoliosis, 12 syndromic). These patients were randomized into one of three groups. In group 1 ( n  = 31 patients), TXA was used topically. TXA was sprayed directly in the wound and sponges soaked with it were used. In group 2 ( n  = 29 patients), intravenous TXA was used intra-operatively. In group 3 ( n  = 23 patients), TXA acid was used neither topically nor systemically. Intraoperative blood loss and the number of blood units transfused were recorded for all patients. The three groups were comparable in the mean age, body weight, operative time, type of deformity, type of osteotomy, number of fused segments, number of screws used. Results: The mean operative time was (240 minute ± 50). The mean blood loss in group 1 was 1353 ± 273 cc, 1271 ±279 cc in group 2, and 1430 ± 311 cc in group 3. The mean number of blood units transfused in group 1 was 2.65 ± 0.587, 2.3 ± 0.571 in group 2, and 3.4 ± 0.5 in group 3. There were no significant differences in intraoperative blood loss and number of units of transfused blood between the first and second groups while there was a significant difference between them and the control group. One patient developed DVT in the intravenous TXA group. Conclusion: Topical TXA is as effective as intravenous TXA and may be used safely to decrease the need for blood transfusion and intraoperative blood loss.